La posiblidad de comprensión. Volver sobre Auschwitz - Blois, María Paula (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This paper presents a reflection on a situation of political violence, based on the physical and symbolic removal of another established as a danger, which seems to have subverted the boundaries of humanity, and changed the domains of thought and action. After considering different dimensions involved (humanity, word, witness), we evaluate the possibility of the current comprehension of this situation. In short, is an attempt consider what place occupies a historical process of political violence in our present.
Keywords: comprehension; political violence; humanity